Synthesis of Tetrahydropyrazolo[4',3':5,6]pyrano[3,4-c]quinolones by Domino Knoevenagel/Hetero Diels–Alder Reactions - Kiamehr, Mostafa; Mohammadkhani, Leyla; Khodabakhshi, Mohammad Reza; Jafari, Behzad; Langer, Peter (Synlett, 2019)
An efficient Lewis acid mediated domino Knoevenagel/hetero Diels–Alder (DKHDA) reaction of pyrazolone derivatives with N-acrylated anthranilic aldehydes was developed, which afforded functionalized tetracyclic tetrahydropyrazolo[4',3':5,6]pyrano[3,4-c]quinolones. The products were formed in good yields and with excellent regio- and stereoselectivity in favor of the cis-configured isomer.
Keywords: domino reaction; regioselectivity; cyclizations; heterocycles; Diels–Alder reaction; Knoevenagel reaction